CONSTRUCTION OF THE APPLICATION OF DOMESTIC VIOLENCE CRIMINAL ACT IN UNREGISTERED MARRIAGES - Yudita Trisnanda; Rodiyah Tangwun; Indah Sri Utari (CV. RADJA PUBLIKA, 2025)
Unregistered marriages are still a common phenomenon in Indonesia, even though marriage registration plays an important role in providing legal certainty and protection, especially in cases of domestic violence (KDRT). Law Number 23 of 2004 concerning the Elimination of Domestic Violence stipulates that the scope of legal protection is only for husband and wife relationships that are legal according to state law. This raises legal problems if violence occurs in unregistered marriages, because victims, especially women, cannot obtain maximum protection. This study aims to examine the construction of the application of law to the crime of domestic violence in unregistered marriages and its urgency in the Indonesian legal system. The research method used is a normative legal approach with a qualitative analysis of relevant laws and case studies. The results of the study indicate the existence of dualism in law enforcement that creates uncertainty and injustice for victims. Therefore, a comprehensive legal construction is needed so that the Law on the Elimination of Domestic Violence can also be applied to cases of violence in marriages that have not been administratively registered but are religiously legal.